Genetic and molecular characterization of P-element-induced mutations reveals that the Drosophila ovarian tumor gene has maternal activity and a variable null phenotype. - Geyer, P.K.; Patton, J.S.; Rodesch, C.; Nagoshi, R.N. (Genetics, 1993)
The mutations in the ovarian tumor (otu) gene arrest oogenesis at several stages in development. A series of deletion mutations in the otu region were characterized, each of which causes the absence or reduction of the otu transcript. These alleles range from the most severe class, which results in ovaries lacking egg cysts, to relatively mild mutations that allow the development of late stage oocytes. Heteroallelic combinations of these mutations demonstrate that the phenotypic complexity of otu mutant ovaries is due to a dosage dependent requirement for otu activity. Reciprocal cross and developmental Northern blot studies suggest a maternal requirement for otu in the development of the female germline. In addition we demonstrate that the otu zygotic null phenotype is variable, ranging from the absence of cysts in the most extreme cases, to the presence of tumorous egg chambers.